Theoretical Problems of Antonymy: the Survey of the 20th Century - Wierzbinski, Jaroslaw (Respectus Philologicus, 2003)
Contemporary state of researches referred to antonymy may be described as a constant search for devices that make it possible to analyze antonyms more effectively. A certain change in the direction of the study of antonymy has been observed. It may be defined as passing from the general language aspect to a concrete-speech embodiment of antonymy. Consequently, the subject domain of the research becomes more extensive – the analysis covers antonymic lines and their functional properties; apart from that antonymy is being examined in connection with the phenomena such as synonymy, polysemy, with an output in larger semantic compounds (synonymo-antonymic blocks). The paper presents the review of the basic directions and results of the research of antonymy in Russian linguistics at the end of the 20th century.
Keywords: lexical semantics; antonymy; synonymy; synonymous and antonymous relations; syntagmo-paradigmatics